2016
DOI: 10.1016/j.pragma.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and space in the virtual world of Second Life

Abstract: Interaction takes place in a spatial context and in many ways is influenced or shaped by this context. Interaction also discursively creates space. There are buildings and rooms that are designed to facilitate specific forms of interaction as for instance in the case of lecture theatres, seminar rooms or assembly halls. The architecture of such rooms, including not only their shape but also the arrangement of furniture and technical equipment, provides affordances that facilitate and structure lectures, class-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…A good match between the avatar and one's real looks helps the user to identify with one's avatar [40]. This in turn helps the user to function authentically and well through the avatar [41]. In designing avatars, users often idealize and complement their own physical features by adding to it details they lack in their physical body.…”
Section: Interaction With Avatar At the 3d Virtual Platformmentioning
confidence: 99%
“…A good match between the avatar and one's real looks helps the user to identify with one's avatar [40]. This in turn helps the user to function authentically and well through the avatar [41]. In designing avatars, users often idealize and complement their own physical features by adding to it details they lack in their physical body.…”
Section: Interaction With Avatar At the 3d Virtual Platformmentioning
confidence: 99%
“…Accordingly, due to the limited body language nature in SL, e.g., signaling to a student or making eye contact, the teachers need to address their learners by calling out the avatars' names. Berger et al [32] reported that their students seldom used body language or eye contact when chatting in SL. To compensate for this, they tend to use other strategies like calling out names in the chat window.…”
Section: Language Training In Sl Vlementioning
confidence: 99%
“…To compensate for this, they tend to use other strategies like calling out names in the chat window. They conclude that "Interaction takes place in a spatial context and in many ways is influenced or shaped by this context … In online virtual worlds, the spatial context of interaction has to be graphically recreated" [32].…”
Section: Language Training In Sl Vlementioning
confidence: 99%
“…They navigate through a three-dimensional world of buildings and objects created by the users. 8 In contrast to many other Massively Multiplayer Online Role Playing Games (MMORPGs), there are no tasks or objectives for the residents, who are free to pursue their own interests, to interact with other residents, organise events such as parties, lectures, discussion circles and so on (see Boellstorff 2008;Abdullah 2015;Brookey and Cannon 2009;Locher et al 2015;Berger et al 2016). The case study presented here is taken from an exploratory study carried out in 2009 and 2010 and presented in some detail in Berger et al (2016).…”
Section: Second Lifementioning
confidence: 99%